2020
DOI: 10.1111/resp.13811
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of control of COPD for risk of exacerbations: An international, prospective study

Abstract: Background and objective: The concept of clinical control in COPD has been developed to help in treatment decisions, but it requires validation in prospective studies. Methods: This international, multicentre, prospective study aimed to validate the concept of control in COPD. Patients with COPD were classified as controlled/uncontrolled by clinical criteria or CAT scores at baseline and followed up for 18 months. The main outcome was the difference in rate of a composite endpoint of moderate and severe exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
19
1
2
Order By: Relevance
“…25 Recent studies have shown the potential for using clinical control as a sensitive marker of health status and exacerbation risk that can easily be used in clinical practice at each clinic visit. 26,27 The magnitude of CCQ change observed with LAMA/LABA therapy in the present report (1.0-point reduction in total CCQ score) is within the range of well-established nonpharmacologic treatment options in COPD, such as pulmonary rehabilitation (0.2-1.3-point reduction in CCQ score) and smoking cessation (0.4-0.5-point reduction in CCQ score), and reflects the mean improvement of CCQ score observed after recovery from COPD exacerbation. 28 In this study, there was a high proportion of treatmentnaïve patients (57%), with a further 28% previously treated with monotherapy only.…”
mentioning
confidence: 99%
“…25 Recent studies have shown the potential for using clinical control as a sensitive marker of health status and exacerbation risk that can easily be used in clinical practice at each clinic visit. 26,27 The magnitude of CCQ change observed with LAMA/LABA therapy in the present report (1.0-point reduction in total CCQ score) is within the range of well-established nonpharmacologic treatment options in COPD, such as pulmonary rehabilitation (0.2-1.3-point reduction in CCQ score) and smoking cessation (0.4-0.5-point reduction in CCQ score), and reflects the mean improvement of CCQ score observed after recovery from COPD exacerbation. 28 In this study, there was a high proportion of treatmentnaïve patients (57%), with a further 28% previously treated with monotherapy only.…”
mentioning
confidence: 99%
“…As previously demonstrated, this indicator is sensitive to changes in the patient's condition, with over 20% of patients presenting changes in control status during a 3monthsfollow-up period (15). Previous studies have shown that these changes in control status are more sensitive to changes in the clinical status of COPD than changes in phenotype, level of risk of GOLD groups A-D (15); and, furthermore, this changes in control status are associated with the risk of future exacerbations (16,28). Our results extend these observations by demonstrating that the control status is associated with the symptom burden and the HRQoL of patients with COPD.…”
Section: Discussionmentioning
confidence: 98%
“…Symptom evaluation was further explored in an international multicentre prospective observational study of 303 patients assessing COPD control to predict future exacerbation risk 36 . Clinical assessment based on recent exacerbations and cardinal COPD symptoms was compared to a COPD Assessment Tool (CAT)‐based method to identify ‘controlled’ versus ‘uncontrolled’ COPD.…”
Section: New Developments In Copdmentioning
confidence: 99%